Perancangan Risk Assessment dengan Metode Kualitatif dan Kuantitatif pada Proyek Pembangunan Ruko di PT XYZ - Djatmiko, Jagad; Puspita, Ika Arum; Yasa, Putu (IAI Nasional Laa Roiba Bogor, 2024)
PT XYZ, a contractor company in the construction sector, is currently working on a project to build 24 shop houses on Jl. Hospital, Bandung City, with a duration of 21 weeks from June to November 2024. This project is divided into several works, including preparation, structure, installation, plumber installation, electrical installation, and wall painting. The project faced challenges such as work accidents, material delays, and conflicts between foremen and subcontractor workers. Due to the lack of effective risk assessment, PT XYZ has difficulty providing a significant response to this problem. Research was conducted to design a risk assessment that includes qualitative and quantitative risk analysis. Qualitative methods are used to create probability impact matrices, risk watch lists and priority risks, while quantitative methods are used to calculate sensitivity analysis related to risk costs. From the research, 186 negative risks and 5 positive risks were found with classifications ranging from insignificant to catastrophic, with the largest risk cost reaching IDR 851,529,000. Researchers also designed contingency plans, checklist forms, material quality checks, and risk reporting to assist PT XYZ in handling project risks.